War, conflict and human rights [ theory and practice - Sriram, Chandra Lekha , 1971-; Herman, Johanna; Martin-Ortega, Olga (Routledge, 2009)
This book examines the tensions and complementaries between protection of human rights and resolution of conflict, considers the scope and effects of human rights violations in a number of contemporary armed conflicts and examines the legal and institutional accountability mechanisms that have been developed.